Floral biology and reproductive potential of Annona hybrid Arka Sahan - Sushmitha, B H; Sakthivel, T; Sankaran, M; Shivashankara, K S; Dhananjaya, M V; Lakshmana Reddy, D C; Venugopalan, R (Journal of Horticultural Sciences, 2024)
Annona hybrid Arka Sahan has become a commercially important fruit in recent times and it needs an assisted pollination to get good size. Studies on floral biology of Annona hybrid Arka Sahan revealed that major bloom occurs during March-April. Most of the flowers start opening during the afternoon and continued till 7.00 pm, while, pollen dehiscence mainly occurred in early morning in the following day. The maximum stigma receptivity was recorded on the day of anthesis. Completely pendulous petal was more common in Arka Sahan flowers resulting = improper pollination. The minimum number of beetles and bees were observed between 7.00 to 8.00 am. Pollen germination and viability were lower at anthesis (5.8% and 44%, respectively) and declined as the day progressed. The pendulous nature of petals eventually brings some un-pollinated stigmas potentially resulting in delayed selfing leading to misshaped fruits.